Is It Worth Switching from Natural Service to Artificial Insemination? A Comparison of Reproductive Performance and Profitability in Dairy Herds - Klibs N. Galvão; Eduardo S. Ribeiro; Jose Eduardo P. Santos (EDIS)
Reproductive efficiency is a key determinant of dairy cow profitability. A considerable portion of dairy producers in the United States still use NS in at least part of their breeding program. This 3-page fact sheet presents the results of papers that compared the reproductive performance and profitability of dairy cows submitted to natural service or a combination of timed AI and natural service. Written by Klibs N. Galvão, Eduardo S. Ribeiro, and Jose Eduardo P. Santos, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, June 2014.